Evaluation of cultural control and resistance‐breeding strategies for suppression of whitefly infestation of cassava at the landscape scale: a simulation modeling approach. Issue 8 (6th April 2020) - Parry, Hazel; Kalyebi, Andrew; Bianchi, Felix; Sseruwagi, Peter; Colvin, John; Schellhorn, Nancy; Macfadyen, Sarina
Abstract: BACKGROUND: The whitefly Bemisia tabaci is an important vector of virus diseases, impacting cassava production in East Africa. To date, breeding efforts in this region have focused on disease resistance. Here we use a spatially‐explicit simulation model to explore how breeding strategies for whitefly resistance will influence the population dynamics of whitefly in the context of regional variation in cassava crop management practices. RESULTS: Simulations indicated that regions with a short cropping cycle and two cropping seasons per year were associated with high whitefly abundance. Nymph mortality and antixenosis resistance mechanisms were more effective than mechanisms that lead to longer whitefly development times. When spatial variation was introduced in heterogeneous landscapes, however, negative consequences of the antixenosis effect were observed in fields containing whitefly susceptible varieties, unless the proportion of whitefly resistant variety in the landscape was low ( 10%) or the amount of matrix in the landscape was high ( 75%). CONCLUSION: We show the importance of considering cropping regime and landscape management context when developing and deploying whitefly‐resistant cassava varieties. Recommendations differ significantly between regions. There may also be unintended negative consequences of higher whitefly densities for whitefly susceptible varieties if uptake of the new variety in a landscape is high, depending on the mechanism of resistance and the landscape context. Furthermore, we show that in some cases, such as where there is substantial fallow combined with a short single‐season crop, the management characteristics of the existing cropping regime alone may be effective at controlling whitefly populations. © 2020 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : We show the importance of considering cropping regime and landscape management context when developing and deploying whitefly‐resistant cassava varieties. In some cases, management practice alone could substantially reduce the pest. © 2020 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.